When I Met You - Forte, Jemma (UK Harlequin MIRA, 2015)
Marianne Baker is happy. Sort of.She's worked at the same job for years (nearly 15, but who's counting), she lives at home with her mum (who is driving her crazy) and sleeps in a single bed (yep, her love life is stalled). Playing the violin is her only real passion - but nobody like her does that for a living.
Keywords: Man-woman relationships -- Terminally ill -- Women violinists